Bridging science and public understanding of risk developing a lexicon for risk warnings in flood, landslide, and typhoon based on local knowledge - Bandiola, Johann Claire D.
Risk communication address different risks that are very vital to everyone. By addressing it means that accurate strategies are needed so that there would be no loss or damage done. Furthermore, one of the most important things that a communicator should do is to make the target audience understand the risk. Most terminologies used in different warning signs are in English and mostly technical. Some are confused between differences in terminologies used. This study explores the use of Binisaya language in creating a communication material that will help address the gaps between the scientific and lay knowledge. The booklet through one-on-one interviews explained terminologies were then reconciled by the researcher. Together with illustrations, proper use of the elements of design the booklet became visual and comprehensive together with the content from the data gathered. The booklet will be most helpful to the community. It can also be used by different agencies concerned with handling risks in a community.